1997
DOI: 10.1128/aac.41.8.1802
|View full text |Cite
|
Sign up to set email alerts
|

Circadian variation in urinary excretion of ciprofloxacin after a single-dose oral administration at 1000 and 2200 hours in human subjects

Abstract: Ciprofloxacin is routinely prescribed to treat a variety of infections, including those of the urinary tract. To achieve optimum therapeutic benefits of the drug, all of the factors which influence its pharmacokinetics and effectiveness need to be determined. This study investigated the urinary excretion kinetics of ciprofloxacin upon oral administration of a single dose of 250 mg at 1000 or 2200 h in 12 healthy human subjects in a crossover design. The urine samples were analyzed for unchanged ciprofloxacin b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…Boulamery et al 966 circadian-time dependent in rodents (Pons et al, 1996). These data agree with previously reported higher values of renal clearance for gentamicin, amikacin, tobramycin, and ampicillin in rodents (Lin et al, 1994;MesnardRici & White, 1998;Rao et al, 1997;Rebuelto et al, 2003aRebuelto et al, , 2003bWhite et al, 1995;Yoshiyama et al, 1993) and cephalexin in dogs (Prados et al, 2007) during the nocturnal activity span.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Boulamery et al 966 circadian-time dependent in rodents (Pons et al, 1996). These data agree with previously reported higher values of renal clearance for gentamicin, amikacin, tobramycin, and ampicillin in rodents (Lin et al, 1994;MesnardRici & White, 1998;Rao et al, 1997;Rebuelto et al, 2003aRebuelto et al, , 2003bWhite et al, 1995;Yoshiyama et al, 1993) and cephalexin in dogs (Prados et al, 2007) during the nocturnal activity span.…”
Section: Discussionsupporting
confidence: 92%
“…Some studies have reported circadian rhythm dependencies in the pharmacokinetics of certain antimicrobial agents (gentamicin, tobramicin, ampicillin, isepamicin, amphotericin B, cephalexin, cephtriaxone, and norfloxacin) in the rat, dogs, or man (Lin et al, 1994;Mesnard-Rici & White, 1998;Prados et al, 2007;Rao et al, 1997;Rebuelto et al, 2003aRebuelto et al, , 2003bWhite et al, 1995;Yoshiyama et al, 1993), but the present work is the first one demonstrating chronopharmacokinetic changes in a betalactam antibiotic agent (i.e., imipenem).…”
Section: Discussionmentioning
confidence: 88%
“…Fasting (n ¼ 10) (Rao et al 1997) and amikacin (Bleyzac et al 2000) urinary elimination was greater in the morning than in the evening. As cephalexin is eliminated by renal excretion, this temporal variation in t 1/2 can be attributed partially to circadian changes in renal functions (Voogel et al 2001).…”
Section: Discussionmentioning
confidence: 96%
“…In addition, there is other diurnal variation relevant to chronokinetics in physiological (gastric emptying, gastrointestinal transit, organ perfusion rates and protein concentrations) and biochemical (pH, enzyme activity) processes (Baraldo 2008). Temporal variation has been demonstrated in humans on other antibiotics, such as amikacin (Bleyzac et al 2000), gentamicin (Choi et al 1999), netilmicin (Lucht et al 1990) and ciprofloxacin (Rao et al 1997). Also, a chronokinetics study has *Corresponding author.…”
Section: Please Scroll Down For Articlementioning
confidence: 97%
“…[81] A significant decrease in the rate and extent of ciprofloxacin excretion following 10 pm administration was observed. [82] Excretion of 17-oxosteroids was also shown to be affected from circadian clock. [83]…”
Section: Pharmacokinetic Outcomes Of Circadian Rhythm: Chronopharmacomentioning
confidence: 99%